Analisis Efektivitas Penerapan Operation Breakdown (OB) di PT. Dan Liris melalui Evaluasi Cycle Time dengan Metode Continuous Improvement - Rebekka Yessica Hutapea; Wesly Siagian (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
PT. Dan Liris has a problem with the production system. Operation Breakdown (OB) is an example of a problem that occurs and has an impact on achieving production targets, delivery accuracy, and product prices. Based on the observations, there was a time mismatch at OB in the production process. The Continuous Improvement method was used as a research method in solving this problem. The data collected by observations, interviews, and literature studies. This research was conducted with the repeated production orders at least three times. Based on the collected data, the actual cycle time were obtained, which were compared with the OB. The data obtained become the basis for determining the solution. The root causes obtained were grouped into five main factors, namely man, machine, method, material, and environment. Of the five factors, two factors that could be used to solve the problem are the man factor and the method. The proposed improvements were the creation of a priority form, a checklist form for the use of machines and attachments, an output form, and the addition of a leadership training agenda. After testing and evaluating the implementation of the improvements, it was found that the forms submitted needed to be revised so that a digital form template was obtained as the final solution that could be used. Keywords: 5M, cycle time, continuous improvement, leadership, operation breakdown